Rotavirus infection in children with different variants allelic polymorphism C> T 13910 gene LCT = Перебіг ротавірусної інфекції у дітей з різними варіантами алельного поліморфізму С >Т 13910 гена лактази - Nezgoda, I.; Naumenko, O. (Journal of Education, Health and Sport, 2016)
Nezgoda I., Naumenko O. Rotavirus infection in children with different variants allelic polymorphism C> T 13910 gene LCT = Перебіг ротавірусної інфекції у дітей з різними варіантами алельного поліморфізму С >Т 13910 гена лактази. Journal of Education, Health and Sport. 2016;6(7):566-578. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.59126 http://ojs.ukw.edu.pl/index.php/johs/article/view/3721 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.07.2016. Revised 25.07.2016. Accepted: 28.07.2016. УДК 616.31-002-053:616-092 ПЕРЕБІГ РОТАВІРУСНОЇ ІНФЕКЦІЇ У ДІТЕЙ З РІЗНИМИ ВАРІАНТАМИ АЛЕЛЬНОГО ПОЛІМОРФІЗМУ С >Т 13910 ГЕНА ЛАКТАЗИ І. І. Незгода, О. М. Науменко Вінницький національний медичний університет імені М. І. Пирогова Резюме. У статті приведені результати обстеження 103 дітей, з діагнозом ротавірусної інфекції. Вивчено та проаналізовано перебіг ротавірусної інфекції в залежності від встановленого генотипу поліморфізму С >Т в позиції 13910 гена лактази (LСT). Встановлено, що найважчий перебіг даної інфекції асоціюється з генотипами, які відповідають за непереносимість лактози С/С-13910 та С/Т-13910. Ключові слова: ротавірусна інфекція, лактазна недостатність, діти. ROTAVIRUS INFECTION IN CHILDREN WITH DIFFERENT VARIANTS ALLELIC POLYMORPHISM C> T 13910 GENE LCT I. Nezgoda, O. Naumenko Vinnitsa National Medical University Pirogov Resume. The article cited the results of a survey of 103 children with a diagnosis of rotavirus infection. Studied and analyzed the course of rotavirus infection depending on the established genotype polymorphism C > T in position 13910 gene lactase (LCT). Found that the most difficult course of infection is associated with genotypes, which are responsible for lactose intolerance C/C-13910 and C/T-13910. Introduction. Rotavirus infection is the dominant etiologic factor in acute intestinal infections in children.Rotavirus protein NSP4 causes deficiency of the enzyme lactase-floryzynhidrolases, while a secondary lactase deficiency. There degree could vary from the minimum till severest. This is due primarily genetically determined lactase activity, as well as percentage in children with determined primary lactase deficiency. Primary lactase deficiency directly correlated with polymorphism C>T at position 13910 lactase gene (LCT). Polymorphism, located above the starting point of transcription, is in the regulatory region of the gene lactase. Genotype S/S-13910 is responsible for almost total absence of lactase. S/T-13910 genotype is associated with low levels of lactase, but it is sufficient for normal Digesting. Genotype T/T-13190 shows high activity of this enzyme. Work on the study of polymorphism C> T at position 13910 lactase gene (LCT) in children with acute intestinal infections in Ukraine were not conducted because the goal of our work is a detailed study of the clinical features of rotavirus infectionin children depending on the genetically determined enzyme activity, based on established genotypes. Materials and methods. The study was conducted at the Vinnytsia Regional Clinical Hospital of Infectious Diseases at the Department of Pediatric Infectious Diseases VNMU named by NI Pirogov. During the period from December 2012 to May 2016 under the supervision was 103 patients aged 1 to 4 years, with a diagnosis of rotavirus infection. The average age (M ± m) patients was 23,4 ± 1,46 months. To establish the etiological factor was performed bacteriological stool examination for detection of pathogenand conditionally pathogenic microflora and enzyme immunoassay stool indication of Rotavirus, Norovirus, Astrovirus and adenoviruses and Clostridium difficille tox A / B and Clostridium difficille GDH. We used test systems from R-Biopharm, Germany. In addition, we studied gene polymorphisms LCT-13910 by polymerase chain reaction with subsequent restriction analysis at the Institute of Hereditary Pathology, Medical Sciences, Lviv, Ukraine. In addition, we studied gene polymorphism at position 13910 LCT in 33 healthy children, residents of the city Vinnytsya and its region, representative by age and gender. In the population studied groups there were three possible options genotypes: homozygous for the C allele patients (CC), homozygous for the T allele person (TT), and children with heterozygous C and T allele (CT). Results of research. When analyzing polymorphism of gene LCT-13910, in children with rotavirus infection was dominant genotype C/C-13910 - in 55,3% of patients, the frequency of genotype C/T-13910 was 34,2%, and only in 10,5% children determined genotype C/C-13910. In more than half of the children surveyed (23 children) diagnosed monoinfection – 57,5%, in the other parts - mixed infection with opportunistic bacteria - 17 patients (42,5%). Genotype C/C-13910, which is associated with almost complete absence of lactase, found in 48 children of the main group, representing 46,6% heterozygote genotype C/T-13910. characterized to low, but sufficient for digestion, lactase activity was detected in 43 children (41,7%), and it is heterozygotes for the polymorphism C>T in position 13910 lactase gene (LCT) are most likely to develop secondary lactoseinsufficiency. In 12 children (11,6%) was established genotype T/T-13910 homozygotes - carriers of this genotype have the highest activity of the lactase. In healthy children genotype frequencies are: genotype C/C-13910 was installed in 66,7% of children, the fate of the genotype C/T-13910 accounted 30%, and only 3,33% of the children in the control group had genotype T/T -13910. Thus, the vast number of examined children has been a genetically determined reduction in lactase activity, which in turn contributes to the peculiarities of course they RVI. One of the prominent symptoms of RVI is hyperthermia. After analyzing temperature response in children with different genotypes LCT gene found that the overwhelming number of children surveyed had a slight fever, but in children with genotypes responsible for lactase deficiency noted the increasingly febrile fever. The average duration of fever was significantly longer (p <0,05) in children with genotype C/C-13910 - 2,6 ± 0,22 days than in children with genotype T/T-13910, which was the duration of hyperthermia 1,66 ± 0,39. Children with genotype C/T-13910 had a temperature response over 2,52 ± 0,29 days. Vomiting is other cardinal symptomof RVI. The average duration of vomiting in children with genotypes associated with hypolactasia was 1,58 ± 0,19 days and 1,76 ± 0,17 days respectively. Children with genotype T/T-13910, which corresponds to the high activity of lactase vomiting lasted an average of 1,08 ± 0,22. Diarrhea is the leading symptom of RVI, the basis of which the underlying metabolic disorders, primarily lactaseinsufficiency, which determines the nature of osmotic diarrhea because the severity of the syndrome is closely associated with the activity disaccharidases, namely lactase in the intestinal lumen. Thus, children with genotype C/C-13910 average duration of diarrhea was 3,45 ± 0,25 days. Children with genotype T/T-13910 had diarrhea for 2,66 ± 0,48 days. Significantly longer diarrheal syndrome was found in heterozygotes polymorphism with genotype C/T-13910 - 4,04 ± 0,24 days (p <0,05), compared with homozygotes T/T-13910. The maximum amount of defecation a day observed in children with genotypes associated with lactose intolerance in children, but among patients with high lactase activity in the intestinal lumen was noted most often from 1 to 3 of episodes of stool per day. Dehydrationis a formidable display of RVI andit'smostly determines the severity of infection in children, because the child's body very quickly lose fluids and electrolytes. Dehydration second stages are often developed in children with genotypes C/C-13910 and C/T-13910, but the overwhelming number of children with genotype T/T-13910 dehydration signs were absent. Conclusions 1. Rotavirus infection in children remains relevant medical and social problem worldwide and Ukraine 2. Among children with RVI 46,6% of patients with genotype carriers proved to C/C-13910, which is associated with almost complete absence of lactase, the figure observed in 1,39 times more likely than healthy children, genotype C/T-13910 that corresponding to low, but sufficient for digestion, lactase activity was detected in 41,7% of patients, whereas genotype T/T-13910, which corresponds to the high activity of the enzyme was installed only in 11,6% of children with RVI, unlike healthy children – 39,4%. 3. Clinical course RVI children with genotype C/C-13910, intoxication syndrome characterized by prolonged fever of 2,61 ± 0,22 days, compared with children with genotype T/T 13910 (1,66 ± 0,39 days at p <0,05) and severe vomiting. 4. Among children with genotype C/T-13910 is marked the longest diarrheal syndrome - 4,04 ± 0,24 days, compared with children with genotype C/C-13910 (3,45 ± 0,25 days) and T/T-13910 (2,66 ± 0,48 days at p <0,05). 5. The course RVI in patients with genotype T/T-13910 is characterized by minimal clinical symptoms, corresponding to mild disease. Key words: rotavirus infection, lactate failure, children.